The Effect of Product Quality, Brand Image and Brand Trust on Customer Satisfaction of Telkomsel SIM Card Users Palembang City - Amelya Yuniar; Roswaty Roswaty; Try Wulandari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This research is to test the variables of product quality, brand image and brand trust to affect the satisfaction of Telkomsel SIM Card customers in Palembang. This research is quantitative and took a sample of 271 respondents from Telkomsel SIM Card users in Palembang City. Data collection techniques in this study by distributing questionnaires using a likert scale. The data sources used are primary data and secondary data. The data analysis technique used is multiple linear analysis which is processed using SPSS version 25 for windows. The findings of this study show that product quality, brand image and brand trust affect the satisfaction of Telkomsel SIM Card customers in Palembang City.